(untitled) (Journal of Parents and Teachers, 2024)
Teenagers often experience emotional states of pain and sadness that impact both their present and future well-being. The author questions whether educational environments and authorities can play a role in helping them manage these emotions and offers practical suggestions for various settings—society, family, and school—to provide support.